Tingkat Pengetahuan Ibu Hamil Tentang Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Pidie Kabupaten Pidie - Faridah Faridah; Alika Alika (Universitas Serambi Mekkah, 2022)
Background: The Wolrd Health Organization (WHO) reports that maternal deaths are estimated at 500,000 deaths annually among which 99% occur in developing countries. Currently in every minute of every day, a mother dies due to pregnancy-related complications, Research Objectives: To know the Maternal Knowledge Level about Pregnant Mother's Class in the Work Area of Pidie Sub-district Pidie Regency 2017. Research Methodology: Research it is descriptive to know the level of knowledge of pregnant mother about pregnant mothers class in working area of Puskesmas Pidie District 2016. Population in this research is all pregnant women in work area of Puskesmas Pidie in November 2017 which amounted to 38 people. sampling using simple random sampling technique that is as much as 38 people. Result: The knowledge of pregnant mother about Ibu Hami Class majority is in enough category as many as 26 people (68,4%) from 38 respondents. Maternal knowledge about class understanding of pregnant women majority in the category enough as much as 22 people (57,9%) from 38 respondents. Maternal knowledge about the benefits of pregnant women's class is mostly in the category of less that is as much as 22 people (57.9%) of 38 respondents. Maternal knowledge about the target of pregnant women majority class in the category of less that is as many as 19 people (50,0%) from 38 respondents. Conclusion: The knowledge of pregnant women about Class majority is in enough category. Suggestion: It is expected that this research can improve the knowledge and understanding of the respondents about the class of pregnant women.Keywords : Knowledge, Pregnant Mom, Pregnant Mother Class